Acaricidal activities of algal extracts against the house dust mite, Dermatophagoides pteronyssinus (Trouessart) - Suneerat RUANGSOMBOON; Jarongsak PUMNUAN (My University, 2016)
The acaricidal activities of seventeen crude algal extracts were tested against the house dust mite Dermatophagoides pteronyssinus (Trouessart) by the contact method at concentrations of 0 (95% ethanol as a control), 0.32, 3.2, and 32μg/cm2. The crude extracts were isolated from cyanobacteria (Oscillatoria sp., Phormidium sp., Spirulina platensis, Spirulina maxima, Fischerella sp., Hapalosiphon sp., Mastigocladopsis sp.), red algae (Acanthophora sp., Gracilaria sp.), green algae (Cladophora sp., Caulerpa lentillifera, Ulva intestinalis, Ulva rigida), and brown algae (Turbinaria sp., Dictyota sp., Padina sp., Sargassum sp.) by means of serial extraction with methanol, dichloromethane, and hexane. Mite mortality was measured after 24h of exposure to the extracts under laboratory conditions at 25±1°C and 86±1% relative humidity. The methanolic crude extracts caused higher mortality than the dichloromethane and hexane extracts. The methanolic crude extracts of Oscillatoria sp., Phormidium sp., Sp. platensis, Sp. maxima, U. intestinalis, Sargassum sp., and Dictyota sp. caused 72.5-99.3% mortality at a concentration of 32μg/cm2. These seven extracts were then reassessed at concentrations of 0, 0.16, 0.32, 1.6, 3.2, 16, 32, 48, and 64μg/cm2. The Oscillatoria sp. and Phormidium sp. extracts showed the highest acaricidal activity, with LC50 values of 0.39 and 0.40μg/cm2, respectively. These results suggest that algal extracts may have potent acaricidal activity.
Keywords: Oscillatoria; Sargassum; Spirulina (dietary supplement); Dichloromethane; Brown algae; Insect Pest Control Strategies